A Delphi consensus among experts on assessment and treatment of disruptive mood dysregulation disorder - Boudjerida, Assia; Guilé, Jean-Marc; Breton, Jean-Jacques; Benarous, Xavier; Cohen, David; Labelle, Réal (Frontiers in Psychiatry, 2024)
: The aim of this study was to explore consensus among clinicians and researchers on how to assess and treat Disruptive Mood Dysregulation Disorder (DMDD). Methods: The Delphi method was used to organize data collected from an initial sample of 23 child psychiatrists and psychologists. Three rounds of closed/open questions were needed to achieve the objective. Results: Fifteen experts in the field completed the whole study. Finally, 122 proposals were validated and 5 were rejected. Globally, consensus was more easily reached on items regarding assessment than on those regarding treatment. Specifically, experts agreed that intensity, frequency, and impact of DMDD symptoms needed to be measured across settings, including with parents, siblings, peers, and teachers. While a low level of consensus emerged regarding optimal pharmacological treatment, the use of psychoeducation, behavior-focused therapies (e.g., dialectical behavior therapy, chain analysis, exposure, relaxation), and systemic approaches (parent management training, family therapy, parent-child interaction therapy) met with a high degree of consensus. Conclusion: This study presents recommendations that reached a certain degree of consensus among researchers and clinicians regarding the assessment and treatment of youths with DMDD. These findings may be useful to clinicians working with this population and to researchers since they also highlight non-consensual areas that need to be further investigated.